The effect of aromatherapy and Su Jok interventions on post-cesarean pain - ALPAR, ŞULE (My University, 2022)
Objective: The aim of this study was to determine the effect of aromatherapy and Su Jok interventions as nonpharmacological methods of relieving pain after cesarean section. Materials and methods: This randomized controlled trial was conducted with 120 women who had cesarean delivery in the gynecology and obstetrics department of a training and research hospital between February 9 and October 2, 2019. The participants were allocated to the aromatherapy group, Su Jok group, Su Jok and aromatherapy group, or control group using block randomization based on parity. Su Jok was performed using buckwheat seed; aromatherapy was applied using lavender, eucalyptus, or rose oil. Data were collected using a participant information form and pain was assessed using the Visual Analog Scale. Results: There was no significant difference between the groups in mean pain levels before or after the intervention, although the control group had less initial pain compared to the intervention groups. However, all three intervention groups showed significant decreases in pain levels immediately and 30 min after the intervention compared to pre-intervention levels (p < 0.05). The intervention in all three groups reduced the level of pain. In particular, the pain level of the Su Jok group reached from moderate to mild. There was no significant change in the control group. Conclusions: Aromatherapy and Su Jok interventions performed separately and simultaneously in addition to routine hospital care were more effective in reducing post-cesarean pain than routine care alone.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; ENTEGRE VE TAMAMLAYICI TIP; Klinik Tıp; Klinik Tıp (MED); INTEGRATIVE & COMPLEMENTARY MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Tamamlayıcı ve Manuel Terapi; Tamamlayıcı ve Alternatif Tıp; Complementary and Manual Therapy; Complementary and Alternative Medicine; Aromatherapy; Cesarean pain; Complementary therapies; Pain; Su jok; POSTOPERATIVE PAIN; THERAPY; REIKI; Aromatherapy; Cesarean pain; Complementary therapies; Pain; Su jok